Satisfaction with perinatal care in women giving birth during the COVID-19 pandemic - Bejer, Agnieszka; Dziedzic, Agnieszka; Fedurko, Weronika; Frydrych, Angelika; Świst, Bernadetta; Schwartz, Marta; Majcher, Angelika; Inglot, Adrian (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The role of a medical team during the perinatal period is significant, since it not only focuses on the patients’ physical health, but also impacts mental wellbeing. The aim of this study is to compare the level of satisfaction with the quality of care provided by healthcare professionals during pregnancy and perinatal period before and during the COVID-19 pandemic. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study was conducted among 102 women who had at least two births, one in the pre-pandemic period and the other during the pandemic. An original questionnaire (53 items) was used to assess the quality of medical care. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The assessment of the quality of medical care, and the emotional and informational support received from medical personnel during pregnancy and perinatal care was significantly higher before the COVID-19 pandemic (p<0.001). During the pandemic, the respondents experienced significantly more anxiety about their health (p=0.027) and their baby’s health (p=0.028) as well as anxiety caused by the lack of a partner during labor (p<0.001). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. It is necessary to further evaluate the quality of medical care for pregnant and perinatal women in order to determine the best possible procedures for the functioning of health care in the time of a pandemic.